Cardiorenal relationships in the focus of risks of atrial fibrillation in patients after acute ST-elevated myocardial infarction (observational program FAKEL) - I. A. Zolotovskaya; I. L. Davydkin; D. V. Duplyakov; V. A. Kokorin (Рациональная фармакотерапия в кардиологии)
Aim. To study markers of renal dysfunction in relation to the likelihood of atrial fibrillation (AF) in patients after ST-segment elevated myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI).Material and methods. The study was conducted with the inclusion of 1 52 patients discharged for outpatient monitoring after STEMI. There were 4 visits: V1 - inclusion visit, V2 - in 12 months, V3 - in 18 months, V4- in 24 months with determination of plasma N-terminal pro-B-type natriuretic peptide (NT-proBNP), cystatin C, erythropoietin, galectin-3, von Willebrand factor (fW), left ventricular ejection fraction. Endpoint: new cases of AF, cardioembolic stroke, deaths.Results. After 24 months 35 patients (23.0%) were diagnosed with AF, 6 of them (3.9%) - developed cardioembolic stroke. The multivariate model of risk factors for AF included indicators: cystatin C (odds ratio [OR] 1.31; 95% confidence interval [95%CI] 1.03-1.67), NT-ProBNP (OR 1.11; 95%CI 1.03-1.19), galectin-3 (OR 0.71; 95%CI 0.55-0.91), fV (OR 0.71; 95%CI 0.55-0.91).Conclusion. The prognostic significance of cystatin C in relation to the risk of AF was established, which should be considered when assessing the prognosis in patients after STEMI.